Describing and evaluating healthcare priority setting practices at the county level in Kenya. (15th April 2018) - Waithaka, Dennis; Tsofa, Benjamin; Kabia, Evelyn; Barasa, Edwine
Summary: Background: Healthcare priority setting research has focused at the macro (national) and micro (patient level), while there is a dearth of literature on meso‐level (subnational/regional) priority setting practices. In this study, we aimed to describe and evaluate healthcare priority setting practices at the county level in Kenya. Methods: We used a qualitative case study approach to examine the planning and budgeting processes in 2 counties in Kenya. We collected the data through in‐depth interviews of senior managers, middle‐level managers, frontline managers, and health partners (n = 23) and document reviews. We analyzed the data using a framework approach. Findings: The planning and budgeting processes in both counties were characterized by misalignment and the dominance of informal considerations in decision making. When evaluated against consequential conditions, efficiency and equity considerations were not incorporated in the planning and budgeting processes. Stakeholders were more satisfied and understood the planning process compared with the budgeting process. There was a lack of shifting of priorities and unsatisfactory implementation of decisions. Against procedural conditions, the planning process was more inclusive and transparent and stakeholders were more empowered compared with the budgeting process. There was ineffective use of data, lack of provisions for appeal and revisions, and limited mechanisms for incorporating community values in the planning and budgeting. Conclusion: County governments can improve the planning and budgeting processes by aligning them, implementing a systematic priority setting process with explicit resource allocation criteria, and adhering to both consequential and procedural aspects of an ideal priority setting process.